Integrasi Nilai Padungku dalam Konseling Analisis Transaksional untuk Meningkatkan Keterampilan Interaksi Sosial Siswa - Sirumpa, Yuyun Lestari; Ratu, Bau; Nurwahyuni, Nurwahyuni; Fitirani, Dian; Arifyadi, Azam; Puswiartika, Dhevy; Lakadjo, Mohamad Awal (Universitas Muhammadiyah Metro, 2026)
This study explores the meaningfulness of group counseling based on Transactional Analysis (TA) integrated with Padungku cultural values in enhancing students' social interaction skills. The research employed a Classroom Action Research (CAR) design using the Hopkins model over two cycles. Participants were 10 tenth-grade students selected through purposive sampling. Data were collected through a social interaction skills instrument, process observations, and student evaluations of counseling services. Results indicated significant improvement, with students progressively shifting from